2023
DOI: 10.3390/cancers15061813
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Revolution of Cancer Treatment with CRISPR Technology

Abstract: Immuno-oncology (IO) and targeted therapies, such as small molecule inhibitors, have changed the landscape of cancer treatment and prognosis; however, durable responses have been difficult to achieve due to tumor heterogeneity, development of drug resistance, and adverse effects that limit dosing and prolonged drug use. To improve upon the current medicinal armamentarium, there is an urgent need for new ways to understand, reverse, and treat carcinogenesis. Clustered regularly interspaced short palindromic rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 74 publications
0
16
0
Order By: Relevance
“…Viral-mediated delivery of drugs by optimizing genes using CRISPR is a recent technology used to treat cancer 29 . Thus, these gene knockout sequences will pave the way for the use of therapeutic drugs to treat various cancers 30 - 32 .…”
Section: Resultsmentioning
confidence: 99%
“…Viral-mediated delivery of drugs by optimizing genes using CRISPR is a recent technology used to treat cancer 29 . Thus, these gene knockout sequences will pave the way for the use of therapeutic drugs to treat various cancers 30 - 32 .…”
Section: Resultsmentioning
confidence: 99%
“…Cancer Therapeutics: CRISPR/Cas9 delivered via viral vectors has been explored as a potential cancer treatment. Studies have demonstrated the successful knockout of oncogenes in cancer cells, inhibiting tumor growth and metastasis (Stefanoudakis et al, 2023) [113] . Additionally, CRISPR/Cas9 has been used to enhance the targeting of cancer cells, increasing the specificity and effectiveness of chemotherapy (Balon et al, 2022) [13] .…”
Section: Phenotypic Outcomes Of Viral Crispr/cas9 Delivery In Recent ...mentioning
confidence: 99%
“…2) We also address the challenges and considerations of this technology, such as off-target effects and regulatory implications, to facilitate its responsible and effective deployment in crop breeding. Advancements in CRISPR technologies have further expanded the toolbox for plant genome editing and transcriptional regulation (Lowder et al, 2015) [75] ; (Wada et al, 2022) [113] ; (Nambiar et al, 2022) [80] . For example, the Cas13a protein has been incorporated, allowing for precise epigenome editing in plants (Dreissig et al, 2017) [36] .…”
Section: Introductionmentioning
confidence: 99%
“…Gene editing technologies aim to restore normal cellular function and halt the progression of CIN. The specificity and precision of these approaches are particularly appealing, as they can potentially spare healthy tissue and minimize adverse effects associated with more invasive treatments [ 70 ].…”
Section: Reviewmentioning
confidence: 99%